2014
DOI: 10.1097/bpo.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Bracing Versus Observation for Early Adolescent Idiopathic Scoliosis

Abstract: Background:Spinal bracing is widely utilized in patients with moderate severity adolescent idiopathic scoliosis with the goal of preventing curve progression and therefore preventing the need for surgical correction. Bracing is typically initiated in patients with a primary curve angle between 25 and 40 degrees, who are Risser sign 0 to 2 and <1-year postmenarchal. The purpose of this study is to determine whether nighttime bracing using a Charleston bending brace is effective in preventing progression of smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…The main reason, we believe, could lie in the relative lower maturity status (premenarchal and Risser 0) of our cohort, which has been identified as one of the key risk factors in predicting curve progression [22,26]. Despite all this, in line with the study by Wiemann et al [13], the results of the current study provide sound evidence supporting that continuous brace treatment could effectively prevent curve progression in more than half of early AIS patients with premenarchal and Risser 0 status.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The main reason, we believe, could lie in the relative lower maturity status (premenarchal and Risser 0) of our cohort, which has been identified as one of the key risk factors in predicting curve progression [22,26]. Despite all this, in line with the study by Wiemann et al [13], the results of the current study provide sound evidence supporting that continuous brace treatment could effectively prevent curve progression in more than half of early AIS patients with premenarchal and Risser 0 status.…”
Section: Discussionsupporting
confidence: 80%
“…Lonstein and Winter [1] reported [24,25] reported the natural history of curve progression that nearly 70 % of IS patients with Risser 0 progressed greater than 5°for curves between 20°and 30°. Wiemann et al [13] evaluated the effectiveness of nighttime brace treatment for Risser 0 and premenarchal AIS patients, and reported that 29 % of them were maintained without curve progression. In our study, the incidence of progression of early AIS (premenarchal and Risser 0) was 38 % (18/48), similar to Lonstein and Winter [1], yet higher than that reported by Nachemson and Peterson [2].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A study in patients with adolescent idiopathic scoliosis (AIS) showed that patients with bracing have less progressive scoliosis when compared to observation group [8] . Another study by Wiemann et al showed the same results [9] . These results have demonstrated the importance of intervention for further prevention of scoliosis progression.…”
Section: Introductionsupporting
confidence: 73%